The Influence of Work Efficiency, Strategic Leadersip, and Organizational Change Mediated by Digital Transformation on the Organizational Performance of Indonesian Army Hospitals - Mustakman, Fauzi; Arafah, Willy; Anggiani, Sarfilianty (International Journal of Business, Economics, and Social Development, 2025)
This quantitative study aims to analyze the mediating role of Digital Transformation on Organizational Performance in Level II Army Hospitals of the Indonesian National Armed Forces (TNI AD), with independent variables including Work Efficiency, Strategic Leadership, and Organizational Change. Data collection was conducted using a cross-sectional approach, employing non-probability sampling with a purposive sampling technique. The unit of analysis comprised individuals at the Top and Middle Management levels of Level II Army Hospitals, with a total population of 318. Data were collected online via Google Forms, yielding 209 valid responses, which were subsequently analyzed using SEM-PLS version 3. The study's findings explain 10 hypotheses, consisting of 7 direct effect hypotheses, of which 4 were supported and 3 were not. Additionally, there were 3 indirect effect hypotheses, where 1 was supported and 2 were not. The most dominant indirect effect hypothesis revealed a positive full mediation effect of Digital Transformation between Organizational Change and Organizational Performance. The theoretical implication indicates that incorporating Digital Transformation as a mediating variable strengthens the impact of Organizational Change while weakening the influence of Work Efficiency and Strategic Leadership on Organizational Performance. Meanwhile, the managerial implication suggests that Digital Transformation in Level II Army Hospitals of TNI AD has a significant impact on Organizational Performance. This study also has limitations, as data were collected only from 14 out of 77 Level II Army Hospitals under the TNI AD healthcare system. The originality of this research lies in the fact that studies examining the influence of Digital Transformation and Strategic Leadership on Organizational Performance in Army Hospitals remain scarce